Metabolic reprogramming and immunosenescence: a new sight for glioma therapy - Fan, Huali; Yang, Shizhuo; Lu, Qing; Chang, Liming (Frontiers in Cell and Developmental Biology, 2026)
Gliomas, the most prevalent primary tumor of the central nervous system, are characterized by a poor prognosis and a high recurrence rate. The glioma microenvironment is highly immunosuppressive, which poses a major obstacle to effective immunotherapy. Metabolic reprogramming is a hallmark of glioma, driving tumor progression and therapy resistance. Key alterations include the Warburg effect, increased glutamine dependency, enhanced pentose phosphate pathway activity, and dysregulated lipid metabolism. Immunosenescence, the age-dependent decline in immune function that contributes to disease pathogenesis, encompasses immune dysregulation, senescence-associated secretory phenotype (SASP) accumulation, and epigenetic changes, which together drive immune cell dysfunction and foster an immunosuppressive microenvironment. Meantime, senescent immune cells may change the metabolic microenvironment, whereas metabolic reprogramming also influence immune system. Thus, this small essay is on the purpose of demonstrating the significance and function of metabolic reprogramming and immunosenescence in gliomas, providing evidence of promising therapeutic strategies.